A new metaheuristic unscented Kalman filter for state vector estimation of the induction motor based on Ant Lion optimizer. Issue 3 (8th May 2018) - Rayyam, Marouane; Zazi, Malika; Barradi, Youssef
Abstract : Purpose: To improve sensorless control of induction motor using Kalman filtering family, this paper aims to introduce a new metaheuristic optimizer algorithm for online rotor speed and flux estimation. Design/methodology/approach: The main problem with unscented Kalman filter (UKF) observer is its sensibility to the initial values of Q and R. To solve the optimal solution of these matrices, a novel alternative called ant lion optimization (ALO)-UKF is introduced. It is based on the combination of the classical UKF observer and a nature-inspired metaheuristic algorithm, ALO. Findings: Synthesized ALO-UKF has given good results over the famous extended Kalman filter and the classical UKF observer in terms of accuracy and dynamic performance. A comparison between ALO and particle swarm optimization (PSO) was established. Simulations illustrate that ALO recovers rapidly and accurately while PSO has a slower convergence. Originality/value: Using the proposed approach, tuning the design matrices Q and R in Kalman filtering becomes an easy task with a high degree of accuracy and the constraints of time cost are surmounted. Also, ALO-UKF is an efficient tool to improve estimation performance of states and parameters' uncertainties of the induction motor. Related optimization technique can be extended to faults monitoring by online identification of their corresponding signatures.